Pengaruh Fraud Pentagon dalam Mendeteksi Kecurangan Laporan Keuangan pada Perusahaan yang Terdaftar di Corporate Governance Perception Index periode 2018-2022 - Noviyanti, Noviyanti; Ersyafdi, Ilham Ramadhan; Prabowo, Muhammad Aras; Mubayyinah, Fira; Aryani, Habsyah Fitri (Jurnal Akuntansi Publik Nusantara, 2024)
The purpose of this study is to test the effect of pressure, opportunity, rationalization, capability and arrogance on financial reporting fraud included in the members of the Corporate Governance Perception Indeks (CGPI) with a research period of 2018-2022 using the associative hypothesis method. The sample used in this study were companies included in the CGPI for the 2018-2022 period. The total sample in this study was 14 companies which were determined using the purposive sampling method. Data analysis was performed by logistik regression. The variables in the study were pressure, opportunity, rationalization, capability and arrogance. The results of this study state that opportunity has a significant positive effect on financial reporting fraud, while pressure, rationalization, capability and arrogance do not have an effect on financial reporting fraud.